Sorbent for removing contaminants from pyrolysis oil

By using inorganic, partially amorphous adsorbent composition to remove plastic waste and recover pollutants from organic materials, the problem of difficulty in removing pollutants in the pyrolytic oil in the prior art is solved, efficient pollutant removal and adsorbent regeneration are achieved, and the quality of hydrocarbon raw materials and the service life of the adsorbent are improved.

CN119585042APending Publication Date: 2025-03-07CLARIANT INT LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202380050374.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-05-05
Filing Date
2023-04-19
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

The prior art is difficult to effectively remove plastic waste and recover pollutants in organic materials, especially nitrogen, oxygen, phosphorus, sulfur and halogen content and heavy metal content in pyrolytic oil, resulting in catalyst deactivation and corrosion problems in downstream oil refining processes.

Method used

Inorganic, at least partially amorphous adsorbent compositions, including minerals, clays, silicates and aluminates, are used to remove contaminants by physical adsorption and chemical adsorption. The adsorbent composition has a high surface area, suitable pore size and total acid sites, and can extend its service life by thermal and anaerobic regeneration methods.

Benefits of technology

It effectively reduces the impurity content in hydrocarbon raw materials, improves the quality of hydrocarbon raw materials, extends the service life of adsorbents, and reduces carbon dioxide emissions.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119585042A_ABST
    Figure CN119585042A_ABST
Patent Text Reader

Abstract

The present invention relates to the use of a sorbent composition for removing impurities from a hydrocarbon feedstock and to a method for regenerating said sorbent after use.
Need to check novelty before this filing date? Find Prior Art

Description

[0001] The present invention relates to the use of an adsorbent composition for removing impurities from a hydrocarbon feedstock and to a method for regenerating the adsorbent after use.

[0002] Today, plastic waste is still mainly landfilled or incinerated to generate heat. Although mechanical recycling may be preferred because it can achieve a more sustainable reuse of resources, this method still leaves some waste streams, and chemical recycling may be an attractive alternative to achieve recycling targets set by many countries. It involves converting waste plastic materials into useful chemicals. An important method for chemically recycling plastic waste is pyrolysis. Pyrolysis is the thermal degradation of plastic waste in an inert atmosphere. It produces products such as pyrolysis gas, liquid pyrolysis oil and coke. Depending on the process conditions, pyrolysis oil can be the main product fraction, and manufacturers strive to maximize its content in the product portfolio. Pyrolysis gas and coke can be used as fuel to generate heat, for example for reactor heating. Pyrolysis oil can be used as a source for synthesis gas production, or it can be processed into chemical raw materials such as ethylene, propylene, C4 fractions, etc. by, for example, (steam) cracking.

[0003] Plastic waste is usually a mixed plastic waste composed of different types of polymers. Polymers often consist of carbon and hydrogen as well as other elements such as chlorine, fluorine, sulfur and nitrogen, which complicates recycling efforts. Elements other than carbon and hydrogen can be harmful during the further processing of crude pyrolysis oil because they can deactivate or poison the catalysts used in the further processing of pyrolysis oil, and are therefore often referred to as pollutants. During (steam) cracking, halogen-containing compounds can cause corrosion damage to the cracking unit because they release hydrogen halides. It is reported that similar corrosion problems also exist in equipment upstream and downstream of the cracking unit, such as heat exchangers, storage containers, etc. Sulfur-containing compounds can deactivate or poison the catalysts used in the cracking unit, or can contaminate the cracking unit products. Nitrogen-containing impurities may also poison downstream catalysts, or they can form explosive NOx when heated. When mixed plastics containing polyvinyl chloride (PVC) are thermally degraded, compounds with double carbon bonds and hydrogen chloride are formed. The hydrogen chloride released from PVC attacks compounds with carbon-carbon double bonds, resulting in the formation of chlorine organic compounds. Plastic waste usually contains additives containing heteroatoms, such as pigments, stabilizers and plasticizers, which are added to improve the performance of polymers. Such additives also often contain compounds containing nitrogen, halogens and sulfur and heavy metals. For example, waste oil, transformer oil, hydraulic oil and mechanical oil may contain heavy metal abrasion products. Pyrolysis oil may also contain metals such as iron (Fe) and metal oxides or other pollutants such as phosphorus (P). (Heavy) metals are often toxic, and the presence of (heavy) metals, metal oxides and other impurities can reduce the quality of pyrolysis oil. In addition, plastic waste can often be unwashed plastics with residues, which can also contain elements other than carbon and hydrogen. Therefore, reducing the nitrogen, oxygen, phosphorus, sulfur and halogen content and (heavy) metal content in pyrolysis oil is crucial for any meaningful processing of pyrolysis oil. In particular, high-quality pyrolysis oil rich in carbon and hydrogen and low in pollutant content is preferred as a raw material to prevent catalyst deactivation and corrosion problems in downstream oil refining processes.

[0004] In addition to plastic waste, recycled or renewable organic materials also contain unwanted contaminants, such as organic oxygen and chlorine, in many cases. Such contaminants need to be removed from the recycled or renewable organic materials prior to catalytic processing of the materials, as such contaminants may negatively affect the catalyst and / or may cause corrosion of process equipment, similar to the problems described above for plastic waste.

[0005] Therefore, many methods have been described that propose to remove pollutants from plastic waste, recycled or renewable materials, many of which use different types of solid adsorbent materials in the purification step.

[0006] WO2020020769A1 (Neste) discloses a method for purifying organic materials (such as plant-based fats and oils, animal-based fats and oils, fossil waste-based oils, waste oils, algae oils and microbial oils) containing chloride (as chloride salts or organic chloride compounds) pollutants. The recovered or renewable organic material is first purified and then hydrotreated at high temperature (270 to 380 ° C), pressure (4 to 20 MPa) and continuous hydrogen flow in the presence of a hydrotreating catalyst to obtain a purified, hydrotreated, recovered or renewable organic material. The method allows the use of low-quality recovered or renewable organic material feeds as raw materials for hydrotreating, such as in the process of producing high-quality renewable fuels and / or chemicals. The purification step can be performed using a solid adsorbent material, which is typically selected from a silica-based adsorbent (such as Trisyl silica) or selected from a metal chloride or metal oxide. After the purification pretreatment step, the adsorbent material is removed from the recovered or regenerable organic material by, for example, filtration, centrifugation and phase separation. WO2020020769A1 does not mention adsorbent regeneration and, apart from mentioning Trisyl silica, does not disclose specific adsorbent details.

[0007] WO2021255591A2 (Sabic) discloses a system and method for treating pyrolysis oil. The pyrolysis oil is treated with an adsorbent to capture and / or adsorb pollutants (e.g., colloids and / or colloid precursors and other heteroatom-containing components, specifically oxygen-containing compounds, nitrogen-containing compounds, chlorine-containing compounds, polynuclear aromatics and heavy tail oils (C20+), silicon-containing compounds and heavy metals), thereby removing pollutants from the pyrolysis oil and producing purified pyrolysis oil. The adsorbent treatment of the pyrolysis oil can be carried out at a temperature between 10 and 100°C and a pressure between 0.1 and 10 bar. The purified pyrolysis oil can then be cracked to produce chemicals including olefins and aromatics. The adsorbent can be activated carbon (carbon), molecular sieves, bleaching clay, silica hydrogel, ionic resin, solidified eggshell powder, or a combination thereof, and can be contained in a guard bed, a purification tower, a stirred tank, and / or a fluidized bed. The adsorbent can be removed from the purified pyrolysis oil by sedimentation, filtration, a cyclone separator, or a combination thereof. WO2021255591A2 proposes that the adsorbent can be regenerated by thermal regeneration, thermal and vacuum regeneration, rinsing with a strong acid or strong base solution, rinsing the adsorbent with a solvent (e.g., rinsing with a polar organic solvent such as tetrahydrofuran (THF)), or a combination thereof. WO2021255591A2 does not give details about the regeneration mentioned, and does not give experimental data for other adsorbents except for specifically suggesting activated carbon or molecular sieves.

[0008] EP3907267A1 (BASF) describes a method for purifying crude pyrolysis oil containing nitrogen, sulfur and halogen from the pyrolysis of plastic waste by subjecting the crude pyrolysis oil to an adsorbent material treatment, which may be activated carbon, alumina, silica, clay material, zeolite, ion exchange resin, absorbent organic polymer or a combination thereof. Contaminants, such as nitrogen-containing, sulfur-containing, halogen-containing and, if present, heavy metal-containing compounds, may be removed from the crude pyrolysis oil by physical adsorption and / or chemical adsorption. The adsorbent bed may be operated at 15 to 35° C. and 0.9 to 1.1 atmospheres. The adsorbed material may be removed from the adsorbent using a selected desorbent (i.e., a material capable of replacing the adsorbate component of the crude pyrolysis oil, such as a polar solvent (e.g., C1-C6 alkanol)) to regenerate the adsorbent material. Amberlyst resins used as adsorbent materials may be regenerated with acid, and activated carbon may be regenerated by thermal treatment using hot steam or nitrogen. The purified pyrolysis oil can be used to produce synthesis gas or hydrocarbon compounds having a lower molecular weight than the pyrolysis oil by cracking the purified pyrolysis oil (steam).

[0009] US2009 / 0156876A1 (ExxonMobil) describes an apparatus and process for thermal cracking of a hydrocarbon feed containing relatively non-volatile hydrocarbons (also known as paraffin-insoluble compounds). These paraffin-insoluble compounds are selectively removed with a solid particulate adsorbent prior to cracking. Examples of solid particulate adsorbents are activated carbon and inorganic oxides, in particular crystalline inorganic oxide molecular sieves, activated alumina, silica, aluminosilicates, clays and bleaching earth. A stream containing aromatic hydrocarbons (e.g., a stream derived from the cracking product) is used to desorb the paraffin-insoluble compounds from the adsorber section at a temperature of 10 to 400° C. and a pressure of 0 to 2760 kPa, thereby regenerating the adsorbent. US2009 / 0156876A1 does not involve recycled or renewable organic hydrocarbon feedstocks.

[0010] Karakhanov et al., Fuel Processing Technology 153 (2016) pp50-57 discloses gamma-alumina-based materials as additives for fluid catalytic cracking (FCC) catalysts. The materials help remove impurities (especially sulfur) from hydrocarbon feedstocks.

[0011] US2008 / 318763 discloses a method for regenerating a silica-containing adsorbent in the context of biofuel production from fatty acid esters. Regeneration involves heating the used adsorbent to 494°C in air for one hour to release the adsorbed pollutants, which in turn can be converted into biofuel or biofuel intermediates.

[0012] WO 2014 / 027336 discloses a neutral adsorbent composition for removing carbon and metal contaminants from feeds, particularly in the context of FCC. The adsorbent composition consists of 30-70 wt% clay and 70-30 wt% silica. The application does not disclose regeneration of the adsorbent.

[0013] There remains a need for alternative and improved processes and suitable adsorbent materials for the sustainable removal of contaminants from organic feedstocks, particularly hydrocarbon feedstocks, and especially from recycled or renewable organic materials.

[0014] It is an object of the present invention to provide a suitable adsorbent composition for purification of crude hydrocarbon feedstocks, thereby overcoming the disadvantages of the prior art processes. In addition, the present invention provides a simple method for extending the useful life of the adsorbent composition, in particular by regenerating the adsorbent after use and recovering the regenerated adsorbent to allow its further use.

[0015] This and other objects of the invention are solved by the subject matter of the independent claims. Further and preferred embodiments of the invention are subject matter of the dependent claims.

[0016] A first object of the present invention is the use of an adsorbent composition for removing impurities from a hydrocarbon feedstock. The adsorbent composition comprises an inorganic, at least partially amorphous material selected from the group consisting of minerals, clays, silicates, aluminates and mixtures thereof. The partially amorphous material has a particle size of at least 150 m 2 / g surface area (according to ASTM UOP964-11), pore size of 2-12 nm, preferably 2-10 nm, more preferably 2-6 nm (according to ASTM UOP964-11), and total acid sites of 50-350 μmol / g (according to NH 3 TPD 150-350℃).

[0017] Both surface area and pore size are measured according to ASTM UOP964-11 with a relative pressure of 0.0006-0.9953 at a temperature of 77.15 K (using the BJH model; average pore diameter = 4 V / A), purging with nitrogen for 30 min, and degassing the sample at 250° C. under vacuum (0.1 bar) for 4 h. From a scientific point of view, the pore size of the present invention corresponds to the peak maximum of the Gaussian distribution curve of the pore width measurement. As known to those skilled in the art, pore size refers to the pore distribution according to the analytical results (in this case N2 porosimetry), which is usually characterized by peak maxima. The average pore width usually produces values ​​around these maxima and indicates the prevalence of these pore sizes in the material. When the peak maximum is outside the measurement range, the average pore width is incorrectly determined. In the context of the present invention, the adsorbent composition is a solid, at least partially amorphous inorganic material. "At least partially amorphous" means that there is a part of the material in which there is no certain long-range order in the crystal structure of the material. In contrast to completely amorphous materials, which show essentially no reflections in X-ray diffraction measurements, at least partially amorphous materials show such reflections (indicating a certain degree of crystallinity). Thus, the partially crystalline or amorphous nature of a solid inorganic material can be determined by X-ray diffraction.

[0018] The adsorbent composition of the present invention is selected from the group consisting of minerals (including clays, natural silicates and natural aluminates), synthetic silicas and synthetic aluminates, and mixtures thereof.

[0019] In particular, suitable minerals are sheet silicates of the kaolin group (e.g. kaolin), the montmorillonite group (e.g. montmorillonite) or other clay minerals (e.g. palygorskite) which have exposed or exposable divalent and / or trivalent metal cations and silanol groups on the mineral surface. The pore size or interlayer spacing of these minerals should be greater than 0.4 nm without collapse during use. In addition, synthetic silicas with exposed silanol groups (especially on the outer particle surface) and synthetic aluminates (usually containing porous gamma-phase alumina) are suitable materials for the present invention. All of the above materials can also be used in the form of mixtures thereof.

[0020] Suitable adsorbent materials can also be regenerated as described when present in the form of a mixture or other solid material, since the reaction between the feedstock and the given adsorbent material occurs on its surface on a microscopic scale, producing regenerated particles that are purification active. For example, a 1:1 mixture of acid-activated bentonite and alumina can also be regenerated.

[0021] The adsorbent composition of the present invention has a 2Surface area of ​​150 m2 (measured according to ASTM UOP964-11, using a relative pressure of 0.0006-0.9953 at a temperature of 77.15 K, purged with nitrogen for 30 min, and the sample degassed at 250° C. under vacuum (0.1 bar) for 4 h). For optimal suitability as an adsorbent composition for the removal of typical impurities in hydrocarbon feedstocks, the surface area is between 150 m2 and 150 m3. 2 / g and 450m 2 / g.

[0022] Likewise, the adsorbent composition has a total acid site of 50-350 μmol / g (in terms of NH 3 TPD 150-350℃).

[0023] Desirably, the adsorbent composition has an average primary particle diameter (D50) of 0.1-100 μm (according to laser diffraction).

[0024] In a preferred embodiment, the adsorbent composition comprises lattice defects ranging from point defects (e.g., substitutional defects where Fe replaces Al), planar defects (e.g., stacking fault planar defects) to three-dimensional defects (e.g., pores), which can be determined, for example, by X-ray diffraction and NMR.

[0025] In a further development of the invention, the adsorbent composition comprises magnesium, aluminum and / or transition metals and / or their oxides and / or mixtures thereof.The metal components in the adsorbent material contribute to the formation of active sites, in particular acid sites.

[0026] Suitable materials may be Trysil (synthetic silica, available from Grace), Tonsil CO 616 GS / L (clay mineral, available from Clariant), and gamma-alumina (synthetic aluminate, available, for example, from Alfa Aesar).

[0027] Suitable hydrocarbon feedstocks for the purposes of the present invention include pyrolysis oils obtained from waste plastics (e.g. from post-consumer waste such as sorted waste streams, as well as industrial waste from different applications such as foil or consumer goods production, electronics, engineering polymers), waste tires, biomass (e.g. wood or lignin-based biomass, used cooking oils, animal fats) and paper or cardboard, general household waste including plastic waste and non-plastic waste.

[0028] Other suitable hydrocarbon feedstocks are used edible oils and animal fats.

[0029] Another suitable hydrocarbon feedstock comprises waste polymer or a monomer solution thereof dissolved in a suitable solvent, wherein the polymer content is at least 10% by weight.

[0030] Generally, it is preferred that the hydrocarbon feedstock comprises a polymer content of at least 25 wt%.

[0031] The term "hydrocarbon feedstock" also includes mixtures of different feedstocks.

[0032] The use according to the invention is suitable for removing impurities or pollutants comprising inorganic and organic nitrogen (e.g. amines), organic oxygen (e.g. organic acids), inorganic and organic chlorine (organochlorine and / or chloride compounds) and organosilicon compounds (e.g. siloxanes). It has been found that the use according to the invention is particularly suitable for removing two or more of these compounds simultaneously. Preferably, the content of both oxygen compounds and chlorine compounds is reduced.

[0033] Those skilled in the art will appreciate that "removing impurities" does not mean that the content of such impurities or contaminants is reduced to zero. In the context of the present invention, removing impurities means substantially reducing the content of such impurities to less than 90% of their original content, preferably less than 60% of their original content. Those skilled in the art will also appreciate that such impurity removal depends on the type of feedstock, the type and amount of adsorbent material, and the contact conditions (e.g., duration, pressure, temperature), and can be adjusted as desired.

[0034] According to the use of the invention, lower quality hydrocarbon feedstocks can be purified so that they can be refined and converted into lighter fractions, for example by cracking.

[0035] Another object of the present invention is a method for regenerating the adsorbent composition of the present invention after use, in particular by regenerating the adsorbent after use and recovering the regenerated adsorbent to allow its reuse. The regeneration method comprises heating the adsorbent composition at a pressure of 0 to 3000 hPa (0-3 bar) in an oxygen-containing atmosphere or in an inert atmosphere at a temperature of 250 to 450° C. for a maximum of 360 minutes, preferably 60 to 180 minutes. The method of the present invention is more sustainable than other methods because it operates in a relatively low temperature range and avoids the use of aromatic-containing streams, acids or organic solvents required in the solvent stripping regeneration methods described in the prior art.

[0036] The gas may be air, carbon monoxide, carbon dioxide, nitrogen or argon, or a mixture thereof, or a mixture of the gas and a small amount of oxygen (usually 0.1 vol% to 21 vol% oxygen).

[0037] The method of regenerating the adsorbent composition allows for anaerobic regeneration of the material. The advantage of anaerobic regeneration is that the deposited carbon compounds (coke) are not converted into carbon dioxide, thereby reducing carbon dioxide emissions and retaining carbon in the process cycle.

[0038] To achieve a final regeneration temperature of 250 to 450°C, a heating rate of about 1 to about 10 K / min is ideally employed. From a technical standpoint, this relatively slow temperature rise is easier to manage than a faster temperature change. In addition, a relatively slow temperature rise tends to help reduce / remove coke deposits in the adsorbent material.

[0039] In another embodiment of the method of the present invention, the temperature is maintained at different ranges for a specific period of time. For example, the temperature is maintained at 175°C for 15 minutes and then at 250°C for 45 minutes.

[0040] It has been found that the adsorbent composition of the present invention can be regenerated multiple times without significantly affecting its adsorption performance for removing impurities from hydrocarbon feedstocks. Contaminants can be removed from pyrolysis oil or other hydrocarbon feedstocks, and the adsorption or removal capacity for these impurities can be restored (at least partially) over multiple cycles, preferably at least 5 cycles.

[0041] BRIEF DESCRIPTION OF THE DRAWINGS

[0042] Figure 1 A schematic diagram of the general experimental setup used for adsorption and regeneration experiments is shown.

[0043] Figure 2 Shown is a graph of the relative adsorption capacity (REL.ADS.CAP., in %) (relative to the original adsorption capacity) of the regenerated adsorbent material samples versus the regeneration temperature (T, in °C) at different regeneration times (15 minutes to 360 minutes).

[0044] Figure 3 Shown are plots of relative chlorine uptake (Cl Up. in %) versus mass turnover rate (MTO in g / g) for samples of virgin adsorbent material and samples of adsorbent material regenerated 1 to 5 times (Reg 1 to Reg 5). Example

[0045] The present invention and its benefits are further explained by the following experimental examples.

[0046] The following analytical methods were used:

[0047] Ammonia temperature programmed desorption (NH 3 TPD 150-350°C) is used to determine the total acidity (total acid sites) in μmol / g. The desorption experiment is carried out after flushing the sample with aqueous ammonia by linearly increasing the temperature from 150°C to 350°C, passing a steady stream of inert gas through the sample, and recording the amount of ammonia desorbed.

[0048] The following test methods were used:

[0049] Devices and conditions

[0050] Figure 1 A general apparatus and process flow diagram is shown in FIG. 1 , in which the abbreviations used have the following meanings:

[0051] IN Gas inlet

[0052] FC 1 Flow controller 1 (for gas supply; 0.1-1 l / h)

[0053] VIC Volume Indicating Flow Controller

[0054] BPV 1 Back pressure valve 1 (to prevent liquid from flowing into the gas part)

[0055] TWV 1 / 2 / 3 / 4 Three-way valve 1 / 2 / 3 / 4

[0056] R 1 / 2 / 3 Reactor module 1 / 2 / 3

[0057] DV 1 Dispensing valve 1

[0058] PI Pressure Indicator

[0059] PRV 1 / 2 Pressure relief valve 1 / 2

[0060] HE 1 Heat exchanger tube 1

[0061] SA sample

[0062] C1 / 2 / 3 / 4 / n Container 1 / 2 / 3 / 4 / n

[0063] VE Ventilation (gas outlet)

[0064] FE Raw Materials

[0065] SO Solvent

[0066] W Waste

[0067] F1 Filter module 1

[0068] P1 Pump 1

[0069] The fixed bed reactor module (R1-3) with the inner core R1 contains the adsorbent material and can be disassembled (e.g. for transport or quick replacement). The inner core R1 has an inner volume of about 8 ml and an inner diameter of 10 mm and is filled with about 5 ml of the adsorbent material, which is fixed with quartz wool. On the inlet side, about 2 ml of glass beads (diameter 500 μm) form a preheating zone, and on the outlet side about 0.5 ml of the same glass beads are placed to form a post-reaction cooling zone, which are also fixed with quartz wool.

[0070] The fixed bed reactor was used for adsorption and regeneration experiments of various feedstocks.

[0071] Prior to the adsorption experiments, the adsorbent was dried at 120°C for 20 min under a constant nitrogen flow (1 L / h) and then set to the adsorption temperature for 1 h under a nitrogen flow (0.2 L / min).

[0072] The adsorption was carried out with a constant liquid hourly space velocity (LHSV) of about 1 at the temperatures given below (mostly 120°C) and at slightly higher pressure (1.4 bar) (for experiments above the boiling point of the pyrolysis oil samples). Samples were collected during the adsorption step by charging the treated feed into the sample flasks after the desired residence time in the reactor column until a set maximum level was reached. After filling one sample flask, the feed stream was automatically directed to the next sample flask. All the treated feed was charged into the sample flasks and the bypass valve was not used until the last sample flask was sufficiently filled.

[0073] Take 4 samples, about 25 ml of each sample, and start regeneration. Stop the oil flow, supply nitrogen (1 liter / hour) to the column, and set the reactor outlet to the waste flask. Regeneration is carried out at ambient pressure (1 bar). After most of the oil is removed from the adsorption bed (about 30 seconds later), the temperature is adjusted to the regeneration temperature given below (usually 250-300°C). When the target regeneration temperature is reached, start the regeneration timer. The heating rate for all experiments is about 10K / min and remains constant. The gas hourly space velocity (GHSV) is about 12,000 (usually between 1,000 and 20,000 to allow a gas contact time of 5 seconds or less, ideally 3 seconds or less).

[0074] After regeneration, the nitrogen flow rate was reduced to 0.1 L / min, the experimental temperature was lowered to room temperature, and the next cycle was started the next day by preheating to the adsorption temperature and lasting for 1 h.

[0075] Example

[0076] The most important properties of the adsorbent material samples were tested and analyzed, and the results are summarized in Table 1:

[0077]

[0078] The hydrocarbon feedstocks used to test the adsorbent materials are as follows:

[0079] Crude pyrolysis oil with different impurity levels was used in the experiments. The oil used was obtained from industrial or pilot processes using waste materials as feedstock and mainly consisted of polymers from organic waste or feedstock with other impurities. The samples were stored under standard conditions (20-22°C) under nitrogen protection.

[0080] The contaminant levels of the tested raw materials are as follows:

[0081] Raw material 1: 250mg / kg Cl, 4200mg / kg O, 1500mg / kg S, 1400mg / kg N

[0082] Raw material 2: 20mg / kg Cl, <500mg / kg O, <1000mg / kg S, <500mg / kg N

[0083] Example 1: Comparison of adsorbent compositions before use and after use and regeneration

[0084] The X-ray powder diffraction patterns (using a copper anode) of the adsorbent composition sample material 6.8 (a granular activated clay material having small mesopores and micropores and Lewis acid sites from transition metals and aluminum) measured before use and after being used to remove impurities from a pyrolysis oil feedstock (120° C., 1.4 bar total pressure) and subsequently regenerated (300° C., 1 bar total pressure, 1 liter / minute N2 flow) showed essentially the same X-ray powder diffraction pattern, indicating that the structure of the composition remained intact after use and thermal regeneration.

[0085] Example 2: Determining the appropriate temperature and time for adsorbent regeneration

[0086] The regeneration of the used adsorbent sample (Material 6.5) was tested using the apparatus and general method described above (at ambient pressure 1 bar). The regeneration of the used adsorbent sample (Material 6.5) was tested by measuring the regeneration of the UV-detectable small molecule (Fe(acac) 3 ) to quantify the relative adsorption capacity of the used, regenerated material relative to the adsorption capacity of the original raw material. The results are shown in Figure 2 as shown in .

[0087] The adsorption capacity recovery increases with increasing temperature, with a maximum value between 300°C and 400°C for the selected adsorbent sample materials. The adsorption capacity recovery tends to decrease after temperatures above 400°C. Temperatures below 200°C do not seem to achieve meaningful adsorption capacity recovery.

[0088] Varying the regeneration time showed that longer regeneration times (up to about 180 minutes) improved the recovery of adsorption capacity; longer times even seemed to have a deteriorating effect (see the 360 ​​minute measurement results).

[0089] For a given sample of adsorbent material, the preferred temperature range is between 200°C and 400°C, and the preferred regeneration time is between 60 minutes and 180 minutes.

[0090] Example 3: Fixed Bed Adsorption of Chlorine Pollutants Using Feedstocks 1 and 2 and Regeneration of Adsorbent Materials

[0091] The regeneration of the used adsorbent sample (M6.8) was tested using the apparatus and general method described above. In experiments using feedstock 1 (described above), the chlorine uptake from the feedstock was measured at a temperature of 120°C, an LHSV of 1 and a pressure of 1.4 bar. The chlorine uptake (mg chlorine / g adsorbent) was recorded for mass-related turnover rates (g feed / g adsorbent) between 5 and 25, with the chlorine uptake being between 0.2 and 1.4.

[0092] Experiments with feedstock 1 show that regeneration times of less than 60 minutes can partially restore the chlorine capacity; regeneration times between 60 minutes and 120 minutes can fully restore the chlorine absorption capacity. Shortening the regeneration time or lowering the temperature can result in a loss of adsorption capacity. Multiple regeneration cycles can be performed.

[0093] Using the apparatus and general method described above, adsorbent sample material M6.8 was used to remove chlorine contaminants from feedstock 2 (described above). The chlorine uptake from the feedstock was measured at a temperature of 120°C, an LHSV of 1 and a pressure of 1.4 bar. Using fresh (original) adsorbent material and adsorbent material after 1 to 5 regeneration cycles (Reg. 1 to 5; regeneration at 300°C using nitrogen and gas at a GHSV of 12,000 for 2 hours), the relative chlorine uptake (expressed as a percentage compared to the original chlorine content) was recorded for mass-related turnover rates (g feed / g adsorbent) between 5 and 25. The relative chlorine uptake is expressed as a percentage of the original chlorine content. Figure 3 and is in the range of 20%-100%.

[0094] The data show that the chlorine absorption capacity of the tested materials can be successfully restored after 5 regeneration cycles for different hydrocarbon feedstocks. As expected, the optimal regeneration temperature depends on the feedstock composition, but generally temperatures between 250°C and 410°C are preferred, while regeneration temperatures of about 300°C appear to be most suitable for restoring the chlorine absorption capacity of the tested adsorbent materials. Regeneration times of up to 120 minutes can restore the chlorine capacity, and regeneration times between 60 minutes and 120 minutes work best.

[0095] Example 4: Fixed Bed Adsorption of Oxygen Pollutants Using Feedstock 1 and Regeneration of Adsorbent Material

[0096] The regeneration of the used adsorbent sample (M6.8) was tested (at ambient pressure 1 bar) using the apparatus and general method described above. In experiments using feedstock 1 (described above), the oxygen uptake from the feedstock was measured at a temperature of 120°C, an LHSV of 1 and a pressure of 1.4 bar. The oxygen uptake (mg oxygen / g adsorbent) was recorded for mass-related turnover rates (g feed / g adsorbent) between 5 and 25, with the oxygen uptake between -15 and +25.

[0097] Experiments with feedstock 1 showed that regeneration times between 30 minutes and 120 minutes and regeneration temperatures of 250°C-300°C can restore the oxygen absorption capacity, with longer times giving better results (120 minutes being preferred). Shortening the regeneration time or lowering the temperature can result in a loss of adsorption capacity. Multiple regeneration cycles can be performed. Surprisingly, when regenerated under optimal conditions (regeneration time 120 minutes; regeneration temperature 300°C), the oxygen absorption capacity of the adsorbent is even higher than that of the original material.

[0098] Example 5: Fixed Bed Adsorption of Nitrogen Pollutants Using Feedstock 1 and Regeneration of Adsorbent Material

[0099] The regeneration of the used adsorbent sample (M6.8) was tested (at ambient pressure 1 bar) using the apparatus and general method described above. In the experiment using feedstock 1 (described above), the nitrogen uptake from the feedstock was measured at a temperature of 120°C, an LHSV of 1 and a pressure of 1.4 bar. The nitrogen uptake (mg nitrogen / g adsorbent) was recorded for mass-related turnover rates (g feed / g adsorbent) between 5 and 25, with the nitrogen uptake being between 2 and 18.

[0100] Experiments using feedstock 1 show that regeneration times between 30 minutes and 120 minutes and regeneration temperatures between 250°C and 300°C can restore nitrogen absorption capacity, with shorter times (30 min-60 min is preferred) and higher temperatures (300°C or higher is preferred) giving better results. Lowering the temperature can result in a loss of absorption capacity. Multiple regeneration cycles can be performed.

[0101] Example 6: Fixed bed adsorption of pollutants (chlorine, oxygen) using feedstock 1 and regeneration of adsorbent material (AC (H620)) - comparative example

[0102] Analogously to Examples 3 and 4, as a comparative example, the removal of chlorine and oxygen pollutants from the feedstock 1 (described above) was measured using activated carbon (AC H620) as adsorbent material. Under the experimental conditions used (temperature 120° C., contact time 5 minutes, pressure 1.4 bar), the material used showed only a slight chlorine pollutant uptake in the case of the original material (between 0.1 and 0.22 mg chlorine / g adsorbent at mass-related turnovers (g feed / g adsorbent) between 5 and 35). The original material did not show any oxygen pollutant uptake. Thermal regeneration was not possible for both pollutants.

[0103] Example 7: Fixed bed adsorption of pollutants (chlorine, oxygen) using feedstock 1 and regeneration of adsorbent material (Trisyl (silicon dioxide))

[0104] The removal of chlorine and oxygen contaminants from feedstock 1 (described above) was measured using silica (Trisyl) as adsorbent material, analogously to Examples 3 and 4. Under the experimental conditions used (temperature 120° C., contact time 5 minutes, pressure 2 bar), the material used showed good chlorine and oxygen contaminant uptake (chlorine contaminant uptake between 0.4 and 1 mg chlorine / g adsorbent at mass-related turnover rates (g feed / g adsorbent) between 10 and 60; oxygen contaminant uptake between 20 and 90 mg oxygen / g adsorbent at mass-related turnover rates (g feed / g adsorbent) between 10 and 60).

[0105] For both pollutants, the thermal regeneration of the adsorbent (300 °C, 1 bar total pressure, 1 L / min N 2 flow) is possible.

[0106] Example 8: Fixed-bed adsorption of oxygen pollutants using feedstock 1 and regeneration of adsorbent material (material 6.6 (highly active bentonite))

[0107] Analogously to Example 4, the removal of oxygen contaminants from feedstock 1 (described above) was measured using a high-activity bentonite (Tonsil Supreme 114FF from Clariant) as adsorbent material. Under the experimental conditions used (temperature 120° C., contact time 5 minutes, pressure 2 bar), the material used showed good oxygen contaminant uptake (oxygen contaminant uptake between 5 and 35 mg oxygen / g adsorbent at a mass-related turnover rate (g feed / g adsorbent) between 5 and 30). The adsorbent was thermally regenerated (temperature 300° C., total pressure 1 bar, gas (N 2 ) flow rates of 1 l / min) are possible.

[0108] Example 9: Fixed bed adsorption of pollutants (chlorine, oxygen) using feedstock 1 and regeneration of adsorbent material (mesoporous γ-alumina)

[0109] Analogously to Example 7, the removal of chlorine and oxygen pollutants from feedstock 1 (described above) was measured using highly mesoporous gamma-alumina (Alfa Aesar) as adsorbent material. Under the experimental conditions used (temperature 120° C., contact time 5 minutes, pressure 2 bar), the material used showed good chlorine and oxygen pollutant uptake (chlorine pollutant uptake between 0.35 and 0.75 mg chlorine / g adsorbent at a mass-related turnover rate (g feed / g adsorbent) between 10 and 50; oxygen uptake between 15 and 80 mg oxygen / g adsorbent at a mass-related turnover rate (g feed / g adsorbent) between 10 and 50). Thermal regeneration of the adsorbent (300° C., 1 bar total pressure, 1 liter / min N2 flow) is possible.

Claims

1. Use of an adsorbent composition for removing impurities from a hydrocarbon feedstock, the adsorbent composition comprising an inorganic, at least partially amorphous material selected from the group consisting of minerals, synthetic silicas, synthetic aluminates and mixtures thereof, characterized in that The material has - At least 150m 2 The surface area of ​​ / g, - a pore size of 2-12 nm, preferably 2-10 nm, more preferably 2-6 nm, Both surface area and pore size were measured according to ASTM UOP964-11 using a relative pressure of 0.0006-0.9953 at a temperature of 77.15 K, purging with nitrogen for 30 min, degassing the sample at 250 °C under vacuum (0.1 bar) for 4 h, and -50-350 μmol / g total acid sites (according to NH3 TPD 150-350°C).

2. The use according to claim 1, characterized in that The mineral is clay.

3. The use according to claim 1 or 2, characterized in that The hydrocarbon feedstock is pyrolysis oil obtained from waste plastics.

4. The method according to any one of the preceding claims, characterized in that Impurities to be removed include organic nitrogen, oxygen, chlorine and silicon compounds.

5. The method according to any one of the preceding claims, characterized in that The adsorbent composition has an average primary particle diameter D50 of 0.1-100 μm, as measured by laser diffraction.

6. The method according to any one of the preceding claims, characterized in that The adsorbent composition comprises lattice defects.

7. The method according to claim 1, characterized in that The sorbent composition comprises magnesium, aluminum and / or transition metals and / or oxides thereof and / or mixtures thereof.

8. A method for regenerating the adsorbent composition according to any one of the preceding claims after use, the method comprising heating the adsorbent composition at a temperature of 250-450°C and a pressure of 0-3000 hPa in an oxygen-containing atmosphere or in an inert gas atmosphere for a period of up to 360 min.

9. The method according to claim 8, characterized in that The heating was performed for a period of 60-180 min.

10. The method according to claim 8 or 9, characterized in that The gas is air, carbon monoxide or carbon dioxide.

11. The method according to claim 8 or 9, characterized in that The gas is nitrogen or argon.

12. The method according to any one of the preceding claims, characterized in that The heating rate to reach the final heating temperature of 250-400° C. is in the range of 1-10 K / min.

Citation Information

Patent Citations

  • Process for purifying a crude pyrolysis oil originating from the pyrolysis of plastic waste

    EP3907267A1

  • System for production and purification of biofuel

    US20080318763A1

  • Apparatus and Process for Cracking Hydrocarbonaceous Feed Treated to Adsorb Paraffin-Insoluble Compounds

    US20090156876A1

  • Adsorbent for removal of con-carbon and contaminant metals present in hydrocarbon feed

    WO2014027336A2

  • Purification of recycled and renewable organic material

    WO2020020769A1